2017
DOI: 10.3390/genes8120373
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Major Capsid Protein of the Archaeal Fusellovirus SSV1: Mutational Flexibility and Conformational Change

Abstract: Viruses with spindle or lemon-shaped virions are rare in the world of viruses, but are common in viruses of archaeal extremophiles, possibly due to the extreme conditions in which they thrive. However, the structural and genetic basis for the unique spindle shape is unknown. The best-studied spindle-shaped virus, Sulfolobus Spindle-shaped Virus 1 (SSV1), is composed mostly of the major capsid protein VP1. Similar to many other viruses, proteolytic cleavage of VP1 is thought to be critical for virion formation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These tools include viral (SSV1) and plasmid-based shuttle systems, as well as CRISPR based gene deletion, mutagenesis, and silencing techniques [ 79 ]. Genetic systems have also been developed for some archaeal viruses, for example, the SSV1 genetic system has provided insightful into the function of archaeal viral genes [ 80 , 81 , 82 ]. Both random and targeted mutagenesis of the SSV1 viral genome surprisingly revealed that only half of the viral genes encoded by the SSV1 genome (16/35 viral genes) are essential for infectivity [ 81 ].…”
Section: Archaeal Virus Life Style and Gene Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These tools include viral (SSV1) and plasmid-based shuttle systems, as well as CRISPR based gene deletion, mutagenesis, and silencing techniques [ 79 ]. Genetic systems have also been developed for some archaeal viruses, for example, the SSV1 genetic system has provided insightful into the function of archaeal viral genes [ 80 , 81 , 82 ]. Both random and targeted mutagenesis of the SSV1 viral genome surprisingly revealed that only half of the viral genes encoded by the SSV1 genome (16/35 viral genes) are essential for infectivity [ 81 ].…”
Section: Archaeal Virus Life Style and Gene Functionsmentioning
confidence: 99%
“…Genetic systems have also been developed for some archaeal viruses, for example, the SSV1 genetic system has provided insightful into the function of archaeal viral genes [ 80 , 81 , 82 ]. Both random and targeted mutagenesis of the SSV1 viral genome surprisingly revealed that only half of the viral genes encoded by the SSV1 genome (16/35 viral genes) are essential for infectivity [ 81 ]. Furthermore, the requirement for a particular viral gene correlates well with its degree of conservation among the Fuselloviridae .…”
Section: Archaeal Virus Life Style and Gene Functionsmentioning
confidence: 99%
“…Transcripts T 4/7/8 , T 9 , and T 1/2 contain most of the core-genome ORFs, while the shell and variable portions of the genome are identifiable in transcripts T 5 and T 6 . The latter are highly flexible regions in the fuselloviruses and contain most of the non-essential genes identified in previous functional genomics studies [ 11 , 34 , 35 ]. Among the genes in the soft-core genome, nine are present in all genomes and constitute the absolute-core (VP1, VP4, D355-integrase, A82, A92, B251-AAA ATPase, C166, A154, and B115), while four genes are present in over 90% of the genomes (VP3, B129, B277, and B78).…”
Section: Genomic Analysismentioning
confidence: 99%
“…A transcriptional activity has been detected also for d335 , encoding the SSV1 integrase. Then, the carrier state of SSV1 is sustained by the expression of a few genes, among which only those encoding the structural capsid proteins (VP1, VP2, and VP3) [ 34 , 52 ] and the integrase have been functionally characterized [ 22 ]. Moreover, a recent study has revealed that most of the lysogenic genes ( vp1, vp2, d355, and a291 ) are apparently essential for SSV1 infectivity, except for c124 and vp3 [ 16 ].…”
Section: Transcriptomic Analysismentioning
confidence: 99%
See 1 more Smart Citation